Cauchy-Kubota-Type integral formulae for the generalized cosine transforms - E. Spodarev (Հայաստանի ԳԱԱ)
The paper considers the action of Radon transforms on Grassmann manifolds for some special functions. These functions are positive powers of the volume of certain parallelepipeds. As a consequence some integral geometric formulas of cauchy-Kubota-type for the generalized cosine transforms on Grasmannians are proved. Some applications of these results in convex and stochastic geometry, stereology and geometric tomography are discussed.
Keywords: Mathematics; Science